GSA Art in Architecture : Selected Art Works 1997-2008. - Avila, Nicole; Caine, William; Finn, Michael; Gibson, Jennifer; Goldstein, Brian; Harrison, Susan; Heartney, Eleanor; Monse, Margaret; Norton, Rachel; Preisser, Janet; Winer, Emma (Washington : GSA (General Services Administration) Washington, 2008)
Kelly, Ellsworth ; LeWitt, Sol ; Michelson, Alan ; Mangold, Robert ; Kim, Mikyoung ; Aycock, Alice ; Shin, Jean ; Sonnier, Keith ; Puryear, Martin ; Lin, Maya ; Held, Al ; Herrera, Arturo ; Manglano-Ovalle, Iñigo ; White, Pae ; Jaudon, Valerie ; Xie, Xiaoze ; Moore, Diana ; Villareal, Leo ; Campbell, Jim ; Rollins, Tim & K.O.S. ; Holzer, Jenny ; Otterness, Tom ; Turrell, James ; Ruscha, Edward ; Fajans, Michael ; Fay, Ming ; Ritchie, Matthew
biog. per kunstenaar
Engels
boek